Adding insult to injury: autoimmune haemolytic anaemia complicated by pulmonary embolism. (14th January 2016) - Woodson, Kevin Andrew; Lee, Yungah; Gopalratnam, Kavitha; Halene, Stephanie
Abstract : Autoimmune haemolytic anaemia (AIHA) is a disease characterised by the production of pathological antibodies that attach to the surface of a patient's own red blood cells, resulting in haemolysis. It can present in either an acute or a chronic manner. In addition to the obvious consequence of anaemia, there are other potentially deadly complications that can arise from AIHA, such as venous thromboembolism (VTE) and pulmonary hypertension. We report a case of a 52-year-old woman who developed a pulmonary embolism (PE) soon after being diagnosed with AIHA. Despite having a very small pulmonary venous clot burden, she developed profound haemodynamic compromise with severe right ventricular dysfunction, which quickly reversed with inhaled nitric oxide treatment. This case makes an interesting observation of cell-free haemoglobin-associated nitric oxide scavenging as a mechanism of pulmonary hypertension and highlights the possible benefit of nitric oxide in treatment.